PENGARUH PERSEPSI KEADILAN DALAM PERPAJAKAN, TEKNOLOGI INFORMASI DAN LOVE OF MONEY TERHADAP ETIKA PENGGELAPAN PAJAK - Lia Amalia (2021)
There have been many tax evasion cases in Indonesia, so that everyone has a different perception of whether or not tax evasion is ethical. This study aims to analyze fairness in taxation, information technology, and love of money on tax evasion ethics. The population used in this study were individual taxpayers who registered at KPP Pratama Pekalongan. The sampling technique used in this study was random sampling. The research data comes from a questionnaire distributed to 100 taxpayers. Data analysis performed using Microsoft Excel 2010 and SmartPLS 3.0. This study indicates that (1) fairness in taxation does not affect the ethics of tax evasion. (2) information technology affects the ethics of tax evasion. (3) love of money affects the ethics of tax evasion.